Exploring the composition of the Pentateuch - Baker, Leslie Scott Jr.; Bergland, Kenneth; Masotti, Felipe A.; Wells, A. Rahel (Bulletin for Biblical Research Supplement, 2020)
Intro -- COVER Front -- Copyright Page -- Table of Contents -- Introduction -- Chapter 1: A Critical Intellectual History of the Historical-Critical Paradigm in Biblical Studies -- Chapter 2: The Exodus, Debt Slavery, and the Composition of the Pentateuch -- Chapter 3: Egyptian Language Practice: A Model for Hebrew Poetic Use? -- Chapter 4: Second-Millennium BC Cuneiform from the Southern Levant and the Literature of the Pentateuch -- Chapter 5: The Hittite Treaty Prologue Tradition and the Literary Structure of the Book of Deuteronomy -- Chapter 6: Memorized Covenantal Instruction and Legal Reuse in Torah -- Chapter 7: The Liturgical Function of Dates in the Pentateuch -- Chapter 8: In the Tradition of Moses:The Conceptual and Stylistic Imprint of Deuteronomy on the Patriarchal Narratives -- Chapter 9: Was Moses the Last Prophet? An Analysis of a Neo-Documentarian Interpretation of Document E -- Chapter 10: Revisiting the Literary Structure (s) of Exodus -- Chapter 11: Was Leviticus Composed by Aaronide Priests to Justify Their Cultic Monopoly -- Chapter 12: The Reception of Priestly Laws in Deuteronomy and Deuteronomy's Target Audience -- Chapter 13: The Relevance of Ezekiel and the Samaritans for Pentateuchal Composition: Converging Lines of Evidence -- Bibliography.